Manipulating Water in High-Performance Hydroxide Exchange Membrane Fuel Cells through Asymmetric Humidification and Wetproofing. Issue 6 (20th February 2015) - Kaspar, Robert B.; Letterio, Michael P.; Wittkopf, Jarrid A.; Gong, Ke; Gu, Shuang; Yan, Yushan
Abstract : Hydroxide exchange membrane fuel cells (HEMFCs) are an emerging low-cost alternative to conventional proton exchange membrane fuel cells. In addition to producing water at the anode, HEMFCs consume water at the cathode, leading to distinctive water transport behavior. We report that gas diffusion layer (GDL) wetproofing strictly lowers cell performance, but that the penalty is much higher when the anode side is wetproofed compared to the cathode side. We attribute this penalty primarily to mass transport losses from anode flooding, suggesting that cathode humidification may be more beneficial than anode humidification for this device. GDLs with little or no wetproofing perform best, yielding a competitive peak power density of 737 mW cm −2 .